The poisoner's ring - Armstrong, Kelley (Armstrong, Kelley. Rip through time novel, 2023)
"A modern-day homicide detective is working as an undertaker's assistant in Victorian Scotland when a serial poisoner attacks the men of Edinburgh and leaves their widows under suspicion. Edinburgh, 1869: Modern-day homicide detective Mallory Atkinson is adjusting to her new life in Victorian Scotland. Her employers know she's not housemaid Catriona Mitchell--even though Mallory is in Catriona's body--and Mallory is now officially an undertaker's assistant. Dr. Duncan Gray moonlights as a medical examiner, and their latest case hits close to home. Men are dropping dead from a powerful poison, and all signs point to the grieving widows... the latest of which is Gray's oldest sister. Poison is said to be a woman's weapon, though Mallory has to wonder if it's as simple as that. But she must tread carefully. Every move the household makes is being watched, and who knows where the investigation will lead. New York Times bestselling author Kelley Armstrong is known for her exquisite world building, and this latest series is no exception. The Poisoner's Ring brings the intricacies of Victorian Scotland alive as Mallory again searches for a 19th-century killer as well as a way home"--